Les stéréotypes des animaux dans les proverbes - Palizhati, Sulaiman (Neophilologica, 2017)
We have studied proverbs of “major impact” in the ouïgour language (Xinjiang in China: they use animal stereotypes to transmit their messages, which are significant for the ouïgour society. “The proverbs code the social knowledge in its popular variant and module the collective behaviours” (Bartmiński, 1998: 77). The proverbs of the Ouïgours are full of animals. It is necessary to know the specifities evoked by the Ouïgours to perceive what the employed images carry in terms of culture and social rules. Some animals are strongly connoted by the Ouïgours. The meanings of particular images, positive or negative, can vary according to the context in which they are used.